PERBAIKAN TEKNIK PENEBANGAN UNTUK MINIMASI LIMBAH PEMBALAKAN DENGAN CARA PENURUNAN TINGGI MULUT TAKIK REBAH - Wesman Endom (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Felling technique in logging operation affect both quantity and quality of logs produced. Improperfelling operation may damage the wood in various ways such as splitting, splintering, and breakage. It leaves more wood wastes in the forest. This study was attempted to reduce wood wastes in felling operation by improving felling technique i.e. through reducing height of undercut.The results showed that the reduction of height of standarized undercut by 30-60% can increase the volume of log produced around 1 %. Calculation of the new method was found that additional cost is relatively small only about Rp. 344,13/m3. Application of this improvement technique, however need a conclusive marketing system.